Analisis Yuridis terhadap Perbuatan Melawan Hukum dalam Kasus Pelanggaran Privasi Data Pribadi di Internet : Legal Analysis of Unlawful Acts In Cases of Personal Data Privacy Violations on The Internet - Liem, Cecilia Chrysilla; Putri, Nadia Herdiana; Pendang, Serlita Ruben; Sinaga, Irene Puteri A. S (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The development of information technology has made it easier to access and exchange data, but on the other hand, it has also increased the risk of personal data privacy violationson the internet. Privacy violations can cause both material and immaterial losses to individuals, so these actions can be classified as unlawful acts (onrechtmatige daad). This study aims to analyze the legal responsibility of perpetrators of personal data privacy violations on the internet from the perspective of Indonesian civil law and examine the application of relevant legal provisions, particularly Article 1365 of the Civil Code and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). The research method used is normative juridical with a statutory and conceptual approach. The results show that violations of personal data privacy on the internet fulfill the elements of an unlawful act because they violate personal rights (privacy rights) guaranteed by law. The PDP Law strengthens the position of victims by providing the right to claim compensation and clarifying the legal responsibilities of controllers and processors of personal data.